PROMOTING TECHNOLOGY ENABLED LEARNING IN THE LIGHT OF NEP 2020 - Patil, Sandeep; Kumar, Pintu (ShodhKosh: Journal of Visual and Performing Arts, 2024)
National Education Policy (NEP) 2020 is a transformational walk towards amalgamating technology into education, endeavoring to promote an inclusive, equitable, and innovative learning ecosystem. This paper investigates how NEP 2020 fosters technology-enabled learning (TEL) approach to address the challenges in education, augment access to education along with preparing the learners for a digital future. NEP 2020 lays emphasis on the incorporation of digital tools, online platforms, and ground-breaking techno-pedagogies to promote better access, quality, and relevance of education across varied socio-economic contexts. The paper explores how NEP 2020 advocates the teacher training emphasizing digital competence development, personalized learning through adaptive technologies, and the use of Artificial Intelligence (AI) and data analytics enhancing educational outcomes. It also deals with the challenges like digital divides, infrastructure limitations, as well as the need for vigorous cyber security measures while implementing TEL. The paper highlights the possible challenges as well as opportunities presented while promoting TEL in the light of NEP 2020.